Accountability and Transparency of the Head of Financial Affairs in the Management of the Village Budget (APBDes) - Sugiyatno Sugiyatno; Nita Suryaningsih; Wardah Jamilah (HK-Publishing, 2024)
Abstract This study aims to analyze the accountability and transparency of the Head of Financial Affairs regarding the management of the Village Budget (APBDes) in Parungkokosan Village, Cikeusik District, Pandeglang Regency. Current trends in village financial governance demand openness and clear accountability to prevent budget misappropriation and enhance public trust. This research employs a descriptive qualitative approach, utilizing data collection methods such as in-depth interviews, observation, and documentation. Informants included the Village Head, the Head of Financial Affairs, the Village Consultative Body (BPD), and local community figures. The collected data were analyzed using techniques involving data reduction, data presentation, and conclusion drawing. The results indicate that the accountability of the Head of Financial Affairs in managing the APBDes generally meets applicable administrative standards, such as the timely preparation of accountability reports. However, transparency faces challenges, particularly regarding the dissemination of budget information—which has not optimally reached all segments of the village community—and limited publication media. Key obstacles identified include the quality of village officials' human resources (HR) regarding mastery of financial information technology systems and a lack of active community participation in budget oversight. The study recommends enhancing human resource capacity through continuous training and optimizing the use of village digital media to ensure transparency in budget information. Keywords: Accountability, Transparency, Head of Financial Affairs, APBDes, Parungkokosan Village.